Parenting through Social Media: The Information Experience of Young Mothers in East Jakarta - Labibah, Kholidah Nurul; Ganggi, Roro Isyawati Permata (Universitas Gadjah Mada, 2024)
The expanding influence of digital information has shape many aspect of life, including parenting How this new sources of knowledge or information shape parents’ way of parenting and its impacts on children’s development need further studies. This study aims to comprehend the parenting information experience of young mothers in East Jakarta. The selection of East Jakarta is based on the fact that the region has the highest birth rate among the five regions in DKI Jakarta, and the occurrence of women marrying before the age of 19 is notably common. Social media is a prominent platform for acquiring information and disseminating knowledge. The method of this study employs a qualitative methodology that integrates a phenomenological approach. The employed data collection methods included semi-structured interviews, observation, and literature analysis. The results indicated that three layers influenced the parenting-related information experience of young women in East Jakarta: features, dimensions, and experiences. The information experience of young moms in East Jakarta is defined by their dissemination of acquired information, time management for information retrieval, and distinction between information necessitating upload and that which does not. Individuals, social media, and investigation are facets of the activities encompassed in information experience. The final layer is experience. This layer elucidates that social media serves as a platform for acquiring knowledge about parenting and its impact on the parenting practices employed. The three layers are interconnected. Each informant possesses a distinct information experience, suggesting that the information experience of young mothers on social media is highly intricate.